Performance, Emotions, and Diplomacy in the United Nations Assemblage in New York. Issue 4 (4th July 2019) - Jones, Alun; Clark, Julian
Abstract : Emotions are crucial to geographies of performance, yet our understanding of their role in diplomacy is not well developed despite many calls, especially from feminist geographers, for greater attention to the study of emotional geopolitics. This article addresses that deficit. We do so by focusing on diplomatic performance as a key component in the anthropology of the state. We argue that performances link statehood with statecraft to create geopolitical power in what we term spaces of possibility . Although state claim making materializes through diplomatic performances, we show that its enactment has been lamentably neglected in terms of its emotional dimensions—even though performance and emotions are constitutive of world making. Representing the state is an active "lived experience" for diplomats that exposes the challenges and vulnerabilities of personal performance through everyday political geographies. Consequently, here we set out a new research agenda for an emotional geopolitics that directly addresses the pivotal role of performance in state claim making through diplomacy. Our focus for this is the topography of action of the United Nations (UN) in New York. Deploying assemblage thinking and using rich empirical data, we illustrate the centrality of material, visceral, and sensual embodiments as they emerge out of and through diplomatic claim making in a range of spaces of possibility. In doing so, we demonstrate how emotions are inseparable facets of everyday UN diplomatic life. Key Words: assemblage, diplomacy, emotions, performance, United Nations.